Chronic exercise normalizes changes in Cav1.2 and KCa1.1 channels in mesenteric arteries from spontaneously hypertensive rats. (23rd January 2015) - Shi, Lijun; Zhang, Hanmeng; Chen, Yu; Liu, Yujia; Lu, Ni; Zhao, Tengteng; Zhang, Lubo
Abstract : Background and Purpose: Regular physical activity is an effective non‐pharmacological therapy for prevention and control of hypertension. However, the underlying mechanisms are not fully understood. Accumulating evidence shows that the elevated vascular tone in hypertension is a consequence of the 'ion channel remodelling' that occurs during sustained high BP. The present study investigated the effects of aerobic exercise on the electrical remodelling of L‐type Ca 2+ (Cav 1.2) and large‐conductance Ca 2+ ‐activated K + (KCa 1.1) channels in mesenteric arteries (MAs) from spontaneously hypertensive rats (SHRs). Experimental Approach: SHRs and normotensive (Wistar‐Kyoto) rats were subjected to aerobic training or kept sedentary, and vascular mechanical and functional properties were evaluated. Key Results: Exercise did not affect the heart weight, but reduced the heart rate and body weight in SHR. In mesenteric arterial myocytes, exercise normalized the increased Cav 1.2 and KCa 1.1 current density in SHRs. Exercise also ameliorated the increased open probability and mean open time of the single KCa 1.1 channel in hypertension. The isometric contraction study revealed that both nifedipine (Cav 1.2 channel blocker) and NS11021 (KCa 1.1 channel activator) induced concentration‐dependent vasorelaxation in MAs precontracted with noradrenaline. Exercise normalized the increased sensitivity of tissues to nifedipine and NS11021 in SHR. Furthermore, protein expression of the Cav 1.2 α1C ‐subunit together with the KCa 1.1 α‐ and β1‐subunit was significantly increased in SHRs; and exercise ameliorated these molecular alterations in hypertension. Conclusions and Implications: Chronic exercise reduces BP and restores vascular function in MAs from SHR, which might be related to the correction of the Cav 1.2 and KCa 1.1 channel remodelling during hypertension.